My Kashmir - "Habibullah, Wajahat" (New Delhi, 2008)
Jammu and Kashmir has been ravaged by conflict for sixty years. Caught in a tug-of-war between India and Pakistan, the state$1 (Ba model of harmony and coexistence for centuries$1 (Bis today riven by conflicts of ethnicity, of religion and national identity; by friction between national and local governments and by rival claims to territory.My Kashmir lays out the intricate web of issues at the root of the crises that engulfed the state at the close of the twentieth century.s
Keywords: Jammu and Kashmir-History and politics